FACULTY MEMBERS’ KNOWLEDGE DEGREE REGARDING RESEARCHGATE WEBSITE AND THEIR ESTIMATIONS FOR ITS EFFECT ON THE DEVELOPMENT OF SCIENTIFIC RESEARCH SKILLS OF INSTRUCTORS AND GRADUATE STUDENTS AT THE UNIVERSITY OF JORDAN - Ibrahim Al-Shara (European Scientific Journal, ESJ, 2015)
The current study aimed at exploring the awareness level of faculty members regarding ResearchGate website and the estimation of its effect on developing their research skills, and that of post graduate students at the University of Jordan. To achieve objectives of the study, the researcher developed research instrument, consisting of 28 items and two open-end questions. To answer questions of the study, averages, T-test and analysis of variance were calculated. Sample of study consisted of (135) members of faculty members. Results implicated that unawareness level of the website by most faculty members was the basic barrier for not using it. Best benefits of using ResearchGate were found to be: interacting with other researchers and being informed with the latest published studies for researchers of similar interests or discipline. Results also revealed differences in developing research skills, in favor of frequent visitors of the site, and those who interact with introduced raised issues. Obvious statistical difference was in favor of faculty members at scientific faculties, to be the most frequent users of the website. According to results, the researcher recommended that the university should provide the necessary infrastructures to help more teaching staff with access to the website, and urge teaching staff for paying more effort to utilize the website, which as a result proved to be of academic benefits for all interested parties.